INDONESIAN ISLAMIC CIVILIZATION IN INTERNET ERA: A MULTIPERSPECTIVE REVIEW - Utomo, Gondo (LPPM IAIN Kudus, 2017)
Islam is not merely a religion, but it also as a civilization. Islam contains complete principles all all aspects of life, so that it became value order guiding human life. But in its development, including in Indonesia, the implementation of Islam civilization value order starts to eroded by amount of things, one of them is due to internet development. Moslem people can easily adopt West behavior which unsuitably aligned with Islamic principles. This article tries to provide description about negative influence of internet on Islamic civilization in Indonesia, and also to provide offers through some perspective for the internet being used to strengthen Islamic civilization. If it stood on true use to share Islam principles, then intenet will have positive impacts for Islamic civilization in Indonesia.